Aphasia Treatments for Spanish Speakers With Aphasia: A Scoping Review - Forero García, Laura Valentina; Bernal Castilla, Maria Paula; Aguilar Mejía, Oscar Mauricio; Quique Buitrago, Yina Magally (Revista de Investigación en Logopedia, 2023)
There is ample research reporting the development of aphasia treatments for English speakers with aphasia. However, less is known about the development of specific treatments for Spanish speakers with aphasia. This scoping review aimed to examine the literature reporting aphasia treatments for Spanish speakers. We conducted a scoping review of studies published between 2011 and 2021 reporting aphasia treatments for Spanish speakers. The scoping review included 19 studies that reported aphasia treatments for Spanish speakers (native speakers or bilinguals with Spanish as their first language). The mean age of the participants was 56.7 years. Nine out of the 19 studies reported single case designs while 10 reported group designs. In addition, 12 studies reported individualized treatments while 7 reported adaptations of treatments previously reported in other languages. On average, the amount of treatment provided to people with aphasia, as reported in the studies, was 14 weeks and 26 sessions (distributed 3 times per week) with a session duration of 1.25 hours. It is important to highlight the research effort in Spanish speakers with aphasia. Nevertheless, the number of studies reporting treatments developed and adapted for Spanish speakers with aphasia in the last decade is extremely limited. There is a need to continue developing research that support evidence-based treatments to respond to the need of Spanish speakers with aphasia, especially in Latin America.